Impact of Astroprincin (FAM171A1) Expression in Oral Tongue Cancer - Wahab, Awais; Almangush, Alhadi; Andersson, Leif C.; Nieminen, Pentti; Salo, Tuula (Frontiers in Oral Health, 2020)
Astroprincin (APCN, FAM171A1) is a recently characterized transmembrane glycoprotein that is abundant in brain astrocytes and is overexpressed in some tumors. However, the expression and role of APCN is unknown in oral tongue squamous cell carcinoma (OTSCC). Aim of this study was to investigate the expression of APCN in OTSCC tissue samples and to analyze possible association of APCN with clinicopathological features and survival rates. This study included 76 patients treated for OTSCC. Expression of APCN in OTSCC tissue sections was examined by immunohistochemistry with a rabbit polyclonal antibody (MAP346) against APCN. All tumors were scored for intensity and percentage of APCN staining at the superficial, middle, and invasive front areas. High expression of APCN was significantly associated with increased tumor size (P = 0.013) and with OTSCC recurrence (P = 0.026). In this pilot study, we observed that the amount of APCN is associated with the size and recurrence of OTSCC. This finding suggests a role of APCN during OTSCC progression.